2018
DOI: 10.1029/2018ja025438
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Nighttime MSTIDS Observed by Optical Thermosphere Imagers at Low Latitudes: Morphology, Propagation Direction, and Wind Filtering

Abstract: Different types of medium‐scale traveling ionospheric disturbances (MSTIDs) have been observed at Cachoeira Paulista (22.4°S; 45.0°W), Brazil, from June 2013 to December 2015, using airglow OI 630.0‐nm images. During the period, 58 MSTIDs were identified and classified as follows: dark band MSTIDs (around 10 events) and periodic MSTIDs (48 events). Dark band MSTIDs present phase velocity between 50 and 200 m/s and propagation direction to northwestward. On the other hand, periodic MSTIDs have phase velocity of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(41 citation statements)
references
References 73 publications
(215 reference statements)
3
37
1
Order By: Relevance
“…We estimated their horizontal wavelength, phase speed and period to be ~ 254 ± 7 km, 190 ± 43 m/s, and 22 min, respectively. The propagation characteristics of these bands is somewhat similar to those of the MSTIDs reported earlier (Garcia et al, ; Shiokawa et al, ; Kubota et al, ; Fukushima et al, ; Shiokawa et al, ; Narayanan et al, ; Figueiredo et al, ). Table summarizes the propagation characteristics of MSTIDs reported in few reports along with that noted in this present study.…”
Section: Observationssupporting
confidence: 85%
“…We estimated their horizontal wavelength, phase speed and period to be ~ 254 ± 7 km, 190 ± 43 m/s, and 22 min, respectively. The propagation characteristics of these bands is somewhat similar to those of the MSTIDs reported earlier (Garcia et al, ; Shiokawa et al, ; Kubota et al, ; Fukushima et al, ; Shiokawa et al, ; Narayanan et al, ; Figueiredo et al, ). Table summarizes the propagation characteristics of MSTIDs reported in few reports along with that noted in this present study.…”
Section: Observationssupporting
confidence: 85%
“…In ionospheric F region, medium‐scale traveling ionospheric disturbances (MSTIDs) that propagate southwestward with phase fronts aligned in the NW‐SE direction in Northern Hemisphere were frequently detected at middle latitude (e.g., Ding et al, ; Figueiredo et al, ; Saito et al, ; Zhou et al, ). The electrodynamic Perkins instability (Perkins, ) can explain the preferred alignment of frontal structures of MSTIDs.…”
Section: Introductionmentioning
confidence: 99%
“…The propagation directions during these seasons are different from the results previously observed by (Kotake et al 2007) who studied MSTIDs over Southern California using GPS network, and Fukushima et al observed that nighttime MSTIDs over "São João do Cariri" in the Southern hemisphere exhibited propagation direction towards the north, northeast, northwest, and southeast. Comparison of the nighttime MSTIDs propagation direction results from Kotake et al (2007), Figueiredo et al (2018b), Paulino et al (2016), and the current study shows an indication that location of the different MSTIDs source could possibly influence propagation direction, and that Perkin instability theory does not always play out in nighttime MSTIDs propagation direction. In addition, we may also possibly say that these propagation direction differences may be as a consequences of wind filtering (Figueiredo et al, 2018b).…”
Section: Discussionmentioning
confidence: 57%
“…Comparison of the nighttime MSTIDs propagation direction results from Kotake et al (2007), Figueiredo et al (2018b), Paulino et al (2016), and the current study shows an indication that location of the different MSTIDs source could possibly influence propagation direction, and that Perkin instability theory does not always play out in nighttime MSTIDs propagation direction. In addition, we may also possibly say that these propagation direction differences may be as a consequences of wind filtering (Figueiredo et al, 2018b).…”
Section: Discussionmentioning
confidence: 57%